Combatting Cyberwarfare Crimes in the European Union - Šepec, Miha; Kočivnik, Maša (European Integration Studies, 2024)
Cyberwarfare crimes constitute a major threat to the security of the European countries. The effects of such attacks could be devastating for the European economy, stability and national security. The question therefore remains, whether the European Union (EU) has effective security measures and strategies against cyberwarfare attacks, and whether it has appropriate legal definitions of such phenomena. Furthermore, does the EU have cooperation measures and institutions for combatting such crimes? In this article we will first present the practical and legal definition of cyberwarfare and its impact on the security of the EU Member States. Then we will analyse the main security measures and strategies of the EU for preventing cyberwarfare attacks, the primary among which are the EU Cybersecurity Act, Directive on the security of network and information systems (NIS) and its second revised version (NIS 2 Directive), and the European Network and Information Security Agency (ENISA).We will continue with substantive legal documents, where the main role is still played by the Directive EU 2013/40/EU on attacks against information systems, which is now almost 11 years old and dated in some aspects. On the procedural level we will analyse the EU cooperation in combatting cyberwarfare attacks through two perspectives (cooperation measures and EU institutions). In the first perspective, we will exam the European Arrest Warrant, the European Evidence Warrant, the European Freezing and Confiscation Order, the European Investigation Order, the European Judicial Network (EJN), and the Schengen Information System (SIS). And in the second, we will present Europol and its European Cyber Crime Centre, Eurojust, and the European Network and Information Security Agency (ENISA). Although the EU has mechanisms in place to combat and prevent cyberwarfare crimes, the legal situation is still far from ideal. The main problem remains the lack of clear legal definition of cyberwarfare crimes and no focused legislation in regard to criminal prosecution of such crimes.